A Literature Review on Perceptions of Organizational Politics (POPs) - S. R. S. N. Sudasinghe, Prabhashini Wijewantha,Mazuki Jusoh, S. M. Ferdous Azam (International Journal of Advanced Science and Technology, 2020)
Perceptions of organizational politics refer to how employees of an organization perceive their work environment as political. This paper is a literature review on the area of perceptions of organizational politics (POPs) covering Western and Sri Lankan studies, and looks into antecedents, consequences, and moderators of POPs.  Studies by foreign authors, as well as the Sri Lankans, both jointly indicate that the presence of organizational politics is a problem for employees working in organizations, and most employees tend to develop negative perceptions towards such political events. Research to date has mainly identified that, employees develop negative perceptions of organizational politics. However, recently there is an emerging perception that employees could also develop positive perceptions about organizational politics. Antecedents of perceptions of organizational politics can be categorized as personal, job related, and organizational influences. Similarly, there are individual and organizational related consequences of perceptions of organizational politics. Further, studies have found many variables acting as moderators for the relationship between POPs and their consequences. This paper presents all these relationships in a nutshell.